Business model development for sustainable apparel consumption: The case of Houdini Sportswear. Issue 4 (1st November 2019) - Holtström, Johan; Bjellerup, Charlotte; Eriksson, Johanna
Abstract : Purpose: The purpose of this paper is to identify key aspects of business model development for sustainable apparel consumption, as actors show an increasing interest in product‒service systems. This purpose should be seen from a retailers' perspective so as to develop sustainable solutions for long-term survival in the apparel industry when meeting consumer preferences for fashion as well as an increasing interest in consuming less. Further, this is from a perspective in an economy where sharing and circularity are potential drivers for changing consumer patterns. Design/methodology/approach: The study is based on the apparel retailer Houdini Sportswear and its business model development from a traditional model of selling sportswear to a more future-oriented model where sustainability is more salient. The data for analysis were collected through interviews with employees within the studied company. The interviews have been guided by overarching themes covering relevant areas of interest for this study. Findings: Overall, the paper shows how sustainability can be included in strategic development, from product idea, product development, production and sales/rental to repair, reuse and finally recycling. The paper also highlights potential obstacles in a developed business model with increased sustainability, including technological platforms, distribution networks for collecting and returning products and consumer consumption preferences. There are a few intertwined factors to be considered on different societal levels to achieve long-term success. Originality/value: This study contributes an increased understanding of how more sustainable solutions can be included when developing business models. While the manufacture, distribution and consumption of clothes have an impact on the environment, some retailers and producers want to reduce this environmental impact. One alternative is to change the way clothes are consumed, to include more sharing and circularity.